2014
DOI: 10.1155/2014/489536
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Sentinel Lymph Node Mapping in Merkel Cell Carcinoma: Systematic Review and Meta-Analysis of Prognostic Studies

Abstract: Aim. To assess through a systematic review and meta-analysis of the literature the prognostic implication of sentinel lymph node mapping in Merkel cell carcinoma (MCC). Materials and Methods. PubMed and SCOPUS databases were searched by using “Merkel AND sentinel” as keywords. All studies with prognostic information regarding SLN mapping in cN0 MCC patients were included. Hazard ratio (HR) for overall survival (OS) and disease free survival (DFS) was used as effect size. Results. SLN biopsy predicted better DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 45 publications
1
11
0
3
Order By: Relevance
“…This did not show any difference in prognosis for the HN subsite compared with other sites. This review also supports the hypothesis that there is a disease-free survival benefit to SLNB compared with observation (HR: 1.64; p = 0.028) [67]. This is an important consideration as the morbidity of uncontrolled regional disease can significantly worsen a patient's quality of life even in the palliative or end of life setting.…”
Section: Merkel Cell Carcinomasupporting
confidence: 73%
“…This did not show any difference in prognosis for the HN subsite compared with other sites. This review also supports the hypothesis that there is a disease-free survival benefit to SLNB compared with observation (HR: 1.64; p = 0.028) [67]. This is an important consideration as the morbidity of uncontrolled regional disease can significantly worsen a patient's quality of life even in the palliative or end of life setting.…”
Section: Merkel Cell Carcinomasupporting
confidence: 73%
“…Response-assessment scans highlighted both metabolic response and lymph node involvement as important prognostic factors for OS (adjusted P , 0.001 and 0.016, respectively). Recent literature has placed an emphasis on sentinel lymph node biopsy for prognostic information and disease-free survival improvement, compared with nodal observation in clinically node negative disease (24). The prognostic value of metabolic response of MCC after definitive treatment is a new observation and suggests that 18 F-FDG PET scans could be included as part of follow-up regimens to provide patients with a more accurate post-treatment prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that a distinct advantage of 18 F-FDG PET was the ability to image the whole body in a single study and the detection of metabolic disease before lymph nodes become clinically evident. Sentinel lymph node biopsy is still, however, important to use in conjunction with 18 F-FDG PET, because these scans have been shown to miss nodal micrometastases (24,27). The low number of patients who had sentinel node evaluation in the response-assessment group is likely due to a high proportion having clinical lymph node involvement, some of the patients being staged before data showing the benefit of sentinel lymph node sampling and some patients having elective nodal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rate (overall regional and distant) was three times higher in sentinel node positive patients as compared with the sentinel node negative ones [4]. The last systematic review by Sadeghi et al in 2014 showed the prognostic importance of SLN mapping in cN0 MCC patients as sentinel node mapping can improve disease free and overall survival in cN0 MCC patients as compared with nodal observation [19].…”
Section: Literature Review and Discussionmentioning
confidence: 99%